Nozzle effects on spray combustion and emissions in compression ignition engines using waste cooking oil biodiesel: A computational fluid dynamics analysis at varying injection pressures - Prem Shanker Yadav; Samer Fikry Abdelfatt Ahmed; Raghvendra Gautam; Hakan Caliskan; Nesrin Caliskan; Hiki Hong (IET Renewable Power Generation)
Abstract This study investigates the spray combustion characteristics of waste cooking oil (WCO) in comparison between a swirl nozzle (SN) and a conventional nozzle (CN) of equal cross‐section. n‐Heptane, methyl decanoate, and methyl‐9‐decenoate were used as WCO substitutes in the simulation. The research primarily focuses on multiphase flow using the Lagrangian‐drop Eulerian‐fluid (LDEF) method, employing an equilibrium phase spray model (EP) for droplet behaviour analysis. The model's efficacy was validated through comparisons with experimental works by other engine researchers. At varying injection pressures, the study found that SN slightly reduced evaporative spray tip penetration but increased the cone angle compared to CN. This suggests early fuel jet disintegration and improved air entrainment due to SN. SN also showed a higher heat release rate and temperature, with soot reduction between 3.20 to 6.72% as injection pressure increased from 100 to 300 MPa. This indicates that SN achieves better air‐fuel mixture than CN. Further, the study discovered that the influence of SN becomes more significant as the rheological properties of WCO lessen under ultra‐high injection pressures.